Step-by-step explanation:
(x-9)²
= (x-9)(x-9)
= x²-9x-9x+81
= x²-18x+81
Y=kx
-5=k(15)
-5/15=k
-1/3=k
now,
y=-1/5x
3=-1/5x
3×5=-1(x)
15=-1(x)
multiplying both sides by -1,we get
-15=x
Answer:
for #2 I'm pretty sure he makes $10 per hour
Answer:
equations:
7x + 4y = 27.35
4x + 5y = 18.75
Step-by-step explanation:
x = burgers
y = sodas
---------------------------------
7x + 4y = 27.35
4x + 5y = 18.75
Answer:
4, 8, 12, 16, 24
Step-by-step explanation:
Replace the x with the x values starting at -2 and use the equation with the new x value.
E.g.
x = -2
y = 4 * -2 + 12
y = 4
Sorry if my explanation isn't the best.